Effect of Leadership Style to Work Motivation: Study on Employee CV. “Lele Indomaju Bersama”, District Malang, Province East Java - Azmi, Muhammad Naufan; Riniwati, Harsuko (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
The role of a leader in an organization is very dominant to influence others in this case his subordinates in such a way that the other person is willing to do the will of the leadership even though personally it may not be liked. It can be concluded that the way the company is very dependent on the leader. However, despite the dominant leader's role, a leader should not ignore the importance of the labor force's role. The method used in this research is descriptive method. Data collection techniques with interviews, observations, and questionnaires. While the type of data used is primary data and secondary data. The analytical tool used is narrative descriptive and multiple linear regression analysis. The results show that leadership style has been able to make good communication, confidence and create work environment and good relationship with other employee so that can motivate and finish work well in work. on CV. “Lele Indomaju Bersama”, autocratic leadership style, democratic leadership, and laissez-faire leadership simultaneously have a positive effect on work motivation. From the results of the t-test is said partially autocratic leadership, democratic leadership, and laissez-faire leadership have a positive effect on work motivation. Based on the results of t-test then obtained laissez-faire leadership is the most dominant factor on employee motivation of CV. “Lele Indomaju Bersama”.